Graphene-based composite master batch, preparation method thereof and application thereof in deodorization filter screen

CN122978475APending Publication Date: 2026-10-27ZHEJIANG GOLDENSEA ENVIRONMENT TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611018489.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,单一吸附材料仅能实现物理吸附,易快速饱和、脱臭寿命短,且饱和后易发生恶臭分子二次释放,无法实现长效净化

Benefits of technology

(1)吸附-催化协同作用:石墨烯作为多功能载体,一方面利用其超大比表面积和吸附性能,配合锆系化学吸附组分实现恶臭分子的快速捕获和富集;另一方面利用其优异的导电性能,作为电子传输介质,降低稀土类氧化催化组分的催化氧化活化能,促进恶臭分子的催化分解,实现“吸附富集→原位催化→无害排放”的闭环脱臭,解决了单一吸附易饱和、单一催化效率低的问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978475A_ABST
    Figure CN122978475A_ABST
Patent Text Reader

Abstract

The application discloses a graphene-based composite master batch, a preparation method thereof and application of the graphene-based composite master batch in a deodorization filter screen, and the preparation method comprises the following steps: graphene is activated by an acid solution, then zirconium-based precursor raw materials and rare earth precursor raw materials are sequentially added to carry out in-situ precipitation, so that graphene-based ternary composite powder is obtained; the graphene-based ternary composite powder is mixed with a matrix resin and a compatilizer, and then is subjected to melt blending, extrusion and granulation, so that the graphene-based composite master batch is obtained. Through a two-step in-situ precipitation method, molecular-level dispersion and bonding of three functional components on the surface of graphene are realized, the composite master batch with a multi-mechanism synergistic deodorization function of 'physical adsorption-chemical adsorption-catalytic oxidation' is prepared, and efficient removal of three foul-smelling gases of ammonia, acetic acid and acetaldehyde can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of adsorption materials technology, and in particular to a graphene-based composite masterbatch, its preparation method, and its application in deodorizing filters. Background Technology

[0002] Deodorizing air filters are a key component for removing indoor odors and improving air quality, and their application demand is increasing. However, mainstream deodorizing filters on the market are still made of single adsorption materials (such as activated carbon and molecular sieves) or simple catalytic materials. They are mainly used to treat common indoor odorous gases, and there is a lack of efficient synergistic removal technologies for the three typical indoor odorous gases: ammonia, acetic acid, and acetaldehyde. For example, patent CN114797313A discloses a composite material air filter device with antibacterial and deodorizing functions. This invention is equipped with a deodorizing mechanism. The exhaust fan blades accelerate the air circulation rate and continuously exchange air, making it easier for the filtered gas to enter the breathable mesh cylinder and be adsorbed and purified by the activated carbon particles and activated carbon filter inside. The spiral stirring blades continuously stir the activated carbon particles, ensuring that the odors come into full contact with them, thereby improving the deodorizing efficiency and quality of the entire device. Patent CN110433870A discloses a photocatalytic material for air filters, its preparation method, and its application. The photocatalytic material is obtained by reacting the surface free groups of a polymer material with a titanate compound in an alcohol solution, followed by hydrolysis. It can be fully exposed on the surface of the filter polymer material and has a high efficiency in degrading air pollutants.

[0003] However, single adsorbent materials can only achieve physical adsorption, are prone to rapid saturation, have short deodorization lifespans, and are susceptible to secondary release of odor molecules after saturation, making long-term purification impossible. Single catalytic materials have weak capture capabilities for low concentrations of ammonia, acetic acid, and acetaldehyde, and their catalytic decomposition efficiency is limited, making it difficult to simultaneously and efficiently remove all three gases. Summary of the Invention

[0004] This invention aims to overcome the aforementioned problems in the prior art by providing a graphene-based composite masterbatch, its preparation method, and its application in deodorizing filters. Through a two-step in-situ precipitation method, the three functional components are dispersed and bonded at the molecular level on the graphene surface, resulting in a composite masterbatch with a multi-mechanism synergistic deodorization function of "physical adsorption-chemical adsorption-catalytic oxidation," which can achieve efficient removal of three malodorous gases: ammonia, acetic acid, and acetaldehyde.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing graphene-based composite masterbatch, comprising the following steps: (1) Activated graphene is obtained by activating graphene with an acid solution; (2) Activated graphene is dispersed in a solvent, zirconium-based precursor raw material is added for in-situ precipitation, and then rare earth precursor raw material is added for further in-situ precipitation. The resulting product is separated, washed, dried and calcined to obtain graphene-based ternary composite powder. (3) The graphene-based ternary composite powder is mixed with the matrix resin and compatibilizer, and then melt-blended, extruded and pelletized to obtain the graphene-based composite masterbatch.

[0006] This invention utilizes a two-step in-situ precipitation method to orderly composite zirconium-based adsorbents and rare-earth catalysts with graphene. A synergistic deodorization system was constructed specifically for the removal of three typical malodorous gases: ammonia, acetic acid, and acetaldehyde, achieving multi-mechanism synergistic removal. This invention first introduces soluble zirconium salt for in-situ precipitation. After acid activation, a large number of oxygen-containing functional groups (-COOH, -OH) are introduced onto the graphene surface. These functional groups partially ionize into negatively charged COO under alkaline conditions. - and O - Zr 4+ These negatively charged sites are strongly electrostatically attracted, and simultaneously interact with -O - Zr-OC covalent bonds are formed, achieving chemical anchoring. Subsequently, rare earth soluble salts are added, and rare earth hydroxide precipitates are simultaneously formed under alkaline conditions. The rare earth elements undergo heterogeneous nucleation and growth with the remaining sites, with more particles distributed as small-sized particles on the graphene surface and in the interstices of zirconium-based particles. Finally, calcination forms a rare earth oxide catalyst. Because Zr... 4+ Zirconium ions possess a high +4 valence charge, strong affinity for oxygen, and high charge density, resulting in strong charge adsorption of negatively charged oxygen-containing functional groups and the formation of stable ionic bonds. Therefore, the binding energy between zirconium-based adsorbents and oxygen-containing functional groups on the graphene surface is significantly higher than that of rare earth ions. This difference determines a clear priority between the two ions when competing for the same anchoring site. In contrast, rare earth ions (such as Ce) have a higher priority. 3+ La 3+ Zirconium oxides typically have a +3 valence, low charge density, and weak electrostatic attraction with oxygen-containing functional groups, resulting in weak bonding stability. Therefore, this invention first deposits a zirconium-based adsorbent on the graphene surface, followed by the deposition of a rare earth catalyst. If the order is reversed, the subsequently added zirconium-based precursor will not be able to find sufficient strong binding sites on the graphene surface for firm anchoring because the strong sites have already been occupied by rare earths. This will lead to non-selective deposition and agglomeration on the surface of the already formed rare earth particles.

[0007] In the catalyst obtained in this invention, graphene, as a high specific surface area carrier, provides abundant physical adsorption sites, rapidly capturing and enriching low concentrations of ammonia, acetic acid, and acetaldehyde molecules, anchoring gas molecules to the fiber surface, thus solving the problems of difficult capture and insufficient contact of low concentration organic gases. Zirconium-based adsorption materials, as chemical adsorption centers, utilize their abundant hydroxyl groups to form strong coordination bonds with alkaline ammonia, achieving selective chemical adsorption of ammonia, thus overcoming the shortcomings of single physical adsorption materials in terms of low adsorption capacity and easy desorption of alkaline gases. Rare earth oxides, as room-temperature catalytic active centers, with the assistance of electron transport from graphene, can efficiently catalytically oxidize adsorbed organic molecules such as acetic acid and acetaldehyde into carbon dioxide and water, achieving complete decomposition of odors.

[0008] This invention combines zirconium-based adsorbents and rare earth catalysts with graphene, resulting in a significant synergistic enhancement effect. 1. Adsorption-catalysis relay synergy: Graphene's high specific surface area solves the problem of insufficient contact with low-concentration organic gases, providing ample reaction substrates for the rare earth catalytic centers. Simultaneously, the catalytic centers decompose adsorbed organic molecules, releasing adsorption sites in both graphene and zirconium-based adsorbents, achieving in-situ regeneration of these sites and significantly extending the material's lifespan. This overcomes the fatal flaws of traditional adsorbents, such as easy saturation and short lifespan. 2. Electron transport synergy: Graphene's excellent conductivity provides a rapid channel for electron transfer during rare earth catalytic reactions, reducing the activation energy and significantly improving the room-temperature catalytic efficiency of rare earth oxides.

[0009] Preferably, the acid solution in step (1) is a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:0.3-0.8, the solid-liquid ratio of the activation treatment is 1g:20-50mL, the activation temperature is 50-80℃, and the activation time is 2-6h.

[0010] Preferably, the zirconium-based precursor raw material in step (2) is a soluble zirconium salt; the rare earth precursor raw material is a soluble salt of cerium and / or lanthanum; and the mass ratio of activated graphene, zirconium-based precursor raw material and rare earth precursor raw material is 1:0.5-3:0.3-2.

[0011] Preferably, the solvent in step (2) is deionized water. After adding zirconium-based precursor raw materials and rare earth precursor raw materials, the mixture is first ultrasonically dispersed for 30-60 minutes, and then the pH value is adjusted to 8.0-10.0. The mixture is then precipitated in situ at 60-90℃ for 2-h. After the second in-situ precipitation reaction, the mixture is aged for 1-2 hours. The calcination temperature is 400-600℃ and the calcination time is 2-4 hours.

[0012] As a preferred option, in step (3), 5-10% graphene-based ternary composite powder, 88-94% matrix resin, and 1-2% compatibilizer are added by mass percentage.

[0013] Secondly, the present invention discloses a graphene-based composite masterbatch prepared using the above-described preparation method.

[0014] Thirdly, this invention discloses the application of the above-mentioned graphene-based composite masterbatch in a deodorizing filter, wherein the deodorizing filter is prepared by: S1: The graphene-based composite masterbatch is used for melt spinning to obtain deodorized monofilament; S2: The obtained deodorized monofilaments are subjected to warp drawing treatment to form weavable warp and weft yarns; S3: The warp and weft yarns are interwoven into a web, and the deodorizing filter is obtained after heat setting.

[0015] Preferably, in S1, graphene composite masterbatch is mixed with resin matrix and melt-spun to form deodorizing monofilament; or graphene composite masterbatch is used as the skin layer and resin matrix is ​​used as the core layer, and melt-spun to form skin-core type deodorizing monofilament.

[0016] Preferably, the traction speed in S2 is 500-1500 m / min.

[0017] As a preferred embodiment, the warp and weft density of the mesh in S3 is 33±2*30±2Pcs / inch; the heat setting temperature is 120-150℃, and the setting time is 10-30s.

[0018] Therefore, the present invention has the following beneficial effects: (1) Adsorption-catalysis synergistic effect: Graphene, as a multifunctional carrier, utilizes its ultra-large specific surface area and adsorption performance to achieve rapid capture and enrichment of odor molecules in conjunction with zirconium-based chemical adsorption components. On the other hand, it utilizes its excellent conductivity as an electron transport medium to reduce the catalytic oxidation activation energy of rare earth oxidation catalytic components, promote the catalytic decomposition of odor molecules, and realize the closed-loop deodorization of "adsorption enrichment → in-situ catalysis → harmless emission", which solves the problems of easy saturation of single adsorption and low efficiency of single catalysis. (2) Strong stability and long service life: Rare earth oxidation catalyst components and zirconium chemical adsorption components are grown in situ on the graphene surface, and then a good interface is achieved with the resin matrix through an interface compatibilizer, which effectively avoids the shedding and agglomeration of catalyst / adsorption components during spinning and use, and improves the structural stability and long-term deodorization of the filter screen. (3) No secondary pollution and wide range of applications: This invention completely decomposes odor molecules into CO2 and H2O through catalytic oxidation, eliminating the need for frequent filter replacement and avoiding pollution caused by secondary release after adsorption saturation; the prepared filter has low wind resistance and good air permeability, and is suitable for deodorization and purification in various scenarios such as indoor, air conditioning, fresh air system, pet environment, and kitchen. Attached Figure Description

[0019] Figure 1 This is the Raman spectrum of the graphene-based ternary composite powder obtained in Example 1 of this invention.

[0020] Figure 2 This is a physical image of the graphene-based deodorizing filter obtained in Example 1 of the present invention.

[0021] Figure 3 This is a test diagram of the water washability of the graphene-based deodorizing filter obtained in Example 2 of the present invention. Detailed Implementation

[0022] The present invention will now be further described with reference to the accompanying drawings and specific embodiments.

[0023] In this invention, unless otherwise specified, all equipment and raw materials are available from the market or commonly used in the industry. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art.

[0024] General Implementation Examples: A method for preparing a deodorizing filter, comprising the following steps: (1) Activated graphene is obtained by activating graphene with an acid solution; (2) Activated graphene is dispersed in a solvent, zirconium-based precursor raw material is added for in-situ precipitation, and then rare earth precursor raw material is added for further in-situ precipitation. The resulting product is separated, washed, dried and calcined to obtain graphene-based ternary composite powder. (3) The graphene-based ternary composite powder is mixed with the matrix resin and compatibilizer, and then melt-blended, extruded and pelletized to obtain the graphene-based composite masterbatch; (4) The graphene-based composite masterbatch is used for melt spinning to obtain deodorized monofilament; (5) The obtained deodorized monofilaments are subjected to warp drawing treatment to form weavable warp and weft yarns; (6) The warp and weft yarns are interwoven into a net and heat-set to obtain the deodorizing filter.

[0025] As a specific implementation method, the acid solution mentioned in step (1) is a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:0.3-0.8. The solid-liquid ratio of the activation treatment is 1g:20-50mL, the activation temperature is 50-80℃, and the activation time is 2-6h. After the activation treatment, the product is dried at a temperature of 60-80℃ for 4-8h.

[0026] In one specific implementation, the zirconium-based precursor raw material in step (2) is a soluble zirconium salt; the rare earth precursor raw material is a soluble salt of cerium and / or lanthanum; and the mass ratio of activated graphene, zirconium-based precursor raw material and rare earth precursor raw material is 1:0.5-3:0.3-2.

[0027] In one specific implementation, the solvent in step (2) is deionized water. After adding zirconium-based precursor raw materials and rare earth precursor raw materials, the mixture is first ultrasonically dispersed for 30-60 minutes, and then the pH value is adjusted to 8.0-10.0. The mixture is then precipitated in situ at 60-90℃ for 2-h. After the second in-situ precipitation reaction, the mixture is aged for 1-2 hours. The separation method is centrifugation, the number of washing cycles is 3-5, the drying temperature is 60-80℃, and the drying time is 6-10 hours. The calcination temperature is 400-600℃, and the calcination time is 2-4 hours.

[0028] In one specific implementation, in step (3), by mass percentage, 5-10% of graphene-based ternary composite powder, 88-94% of matrix resin, and 1-2% of compatibilizer are added; the mixing temperature is 80-100℃, the mixing time is 10-20 min; the extrusion temperature of melt blending is 170-200℃, and the screw speed is 100-200 r / min.

[0029] In one specific implementation, in step (4), graphene composite masterbatch and resin matrix are mixed and melt-spun to form deodorized monofilament; or graphene composite masterbatch is used as the skin layer and resin matrix is ​​used as the core layer, and melt-spun to form a skin-core type deodorized monofilament; the amount of graphene composite masterbatch added is 10-15wt%, the amount of resin matrix added is 85-90wt%, the melt spinning temperature is 180-250℃, the draw ratio is 5-7 times, the cold water tank temperature is 25-45℃, the winding speed is 100-120m / min, and the setting temperature is 100-150℃.

[0030] In one specific implementation, the traction speed in step (5) is 500-1500 m / min.

[0031] In one specific implementation, the warp and weft density of the net in step (6) is 33±2*30±2Pcs / inch; the heat setting temperature is 120-150℃, and the setting time is 10-30s.

[0032] Example 1:

[0033] A method for preparing a graphene-based deodorizing filter, comprising the following steps: (1) Preparation of activated graphene powder: Graphene was placed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:0.5, with a solid-liquid ratio of 1:30 g / mL, and stirred at a constant temperature of 65℃ for 4h. After the reaction was completed, the graphene was washed with deionized water by centrifugation until the filtrate was neutral, dried under vacuum at 70℃ for 6h, and then ground to obtain activated graphene powder. (2) Preparation of graphene-based ternary composite powder: Activated graphene powder was dispersed in deionized water at a mass-to-volume ratio of 1 g:50 mL and ultrasonically dispersed for 45 min. The pH of the system was adjusted to 9.0 using ammonia water and kept in a constant temperature water bath at 75℃. ZrOCl2·8H2O was added first and stirred at a constant temperature for 3 h. Then Ce(NO3)3·6H2O was added and stirred at a constant temperature for another 3 h. The mixture was then allowed to stand for 1.5 h to age. After centrifugation, the powder was washed four times with deionized water, dried at 70℃ for 8 h, and then calcined at 500℃ for 3 h. The powder was then ground and sieved to obtain graphene-based ternary composite powder. The mass ratio of activated graphene, ZrOCl2·8H2O, and Ce(NO3)3·6H2O was 1:1.5:0.8. The Raman spectrum of the obtained graphene-based ternary composite powder is shown below. Figure 1 As shown in the figure, the Raman spectrum exhibits a typical D peak (~1356 cm⁻¹). -1 G peak ~1587 cm -1 ), 2D peak (~2300 cm) -1 The characteristics are consistent with the Raman response law of graphene materials; (3) Preparation of high-load deodorization masterbatch: Graphene-based ternary composite powder, polypropylene (PP) matrix resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S), and maleic anhydride-grafted PP interface compatibilizer were mixed at a mass ratio of 7:91.5:1.5 and added to a high-speed mixer and mixed at 90°C for 15 min; then fed into a twin-screw extruder for melt blending, with an extrusion temperature of 185°C and a screw speed of 150 r / min; after water cooling, pelletizing, and drying, high-load deodorization masterbatch was obtained. (4) Preparation of graphene deodorized monofilament: The deodorization masterbatch and pure PP resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S) were mixed uniformly at a mass ratio of 12:88 and fed into a melt spinning equipment; the spinning temperature was 195℃, and after spinning, the fibers were stretched with a stretch ratio of 5 times and a winding speed of 110m / min to obtain graphene deodorized monofilament; (5) Warp drawing treatment: The graphene deodorized monofilaments are drawn and treated at a speed of 800 m / min and the monofilament tension is controlled at 0.10~0.30 cN / dtex to obtain uniform and stable warp and weft yarns; (6) Warp and weft interlacing to form a net: the warp and weft yarns after being drawn are introduced into a high-speed rapier loom, the loom speed is controlled at 15m / min, and the warp and weft interlacing is used to form a filter net fabric; the warp and weft density of the finished filter net is 33±×30±2 threads / inch; (7) Heat setting treatment: The filter fabric is fed into a heat setting device at a setting temperature of 135℃ and held for 20 seconds to improve the dimensional stability of the fabric and the cross-bonding strength of the filaments, thus obtaining a graphene-based deodorizing filter. The actual product is shown in the figure. Figure 2 As shown in the image.

[0034] Example 2:

[0035] A method for preparing a graphene-based deodorizing filter, comprising the following steps: (1) Preparation of activated graphene powder: Graphene was placed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:0.5, with a solid-liquid ratio of 1:30 g / mL, and stirred at a constant temperature of 65℃ for 4h. After the reaction was completed, the graphene was washed with deionized water by centrifugation until the filtrate was neutral, dried under vacuum at 70℃ for 6h, and then ground to obtain activated graphene powder. (2) Preparation of graphene-based ternary composite powder: Activated graphene powder was dispersed in deionized water at a mass-volume ratio of 1g:50mL and ultrasonically dispersed for 45min; the pH of the system was adjusted to 9.0 with ammonia water and kept in a constant temperature water bath at 75℃; ZrOCl2·8H2O was added first and stirred at a constant temperature for 3h, then Ce(NO3)3·6H2O was added and stirred at a constant temperature for another 3h, and then allowed to stand for aging for 1.5h; after centrifugation, the powder was washed 4 times with deionized water, dried at 70℃ for 8h, and then calcined at 500℃ for 3h, ground and sieved to obtain graphene-based ternary composite powder; the mass ratio of activated graphene, ZrOCl2·8H2O and Ce(NO3)3·6H2O was 1:3:2. (3) Preparation of high-load deodorization masterbatch: Graphene-based ternary composite powder, polypropylene (PP) matrix resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S), and maleic anhydride-grafted PP interface compatibilizer were mixed at a mass ratio of 10:88:2 and added to a high-speed mixer and mixed at 90°C for 15 min; then fed into a twin-screw extruder for melt blending, with an extrusion temperature of 185°C and a screw speed of 150 r / min; after water cooling, pelletizing, and drying, high-load deodorization masterbatch was obtained. (4) Preparation of graphene deodorized monofilament: The deodorization masterbatch and pure PP resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S) are mixed evenly at a mass ratio of 15:85 and fed into a melt spinning equipment; the spinning temperature is 195℃, and after spinning, the fibers are stretched with a stretch ratio of 5 times and a winding speed of 110m / min to obtain graphene deodorized monofilament. (5) Warp drawing treatment: The graphene deodorized monofilaments are drawn and treated at a speed of 800 m / min and the monofilament tension is controlled at 0.10~0.30 cN / dtex to obtain uniform and stable warp and weft yarns; (6) Warp and weft interlacing to form a net: the warp and weft yarns after being drawn are introduced into a high-speed rapier loom, and the loom speed is controlled at 10-20m / min. The warp and weft yarns are interlaced to form a filter net fabric; the warp and weft density of the finished filter net is 33±×30±2 threads / inch; (7) Heat setting treatment: The filter fabric is sent into the heat setting equipment, the setting temperature is 135℃, and the heat setting is maintained for 20s to improve the dimensional stability of the fabric and the cross-bonding strength of the filaments, so as to obtain the graphene-based deodorizing filter.

[0036] Example 3:

[0037] A method for preparing a graphene-based deodorizing filter, comprising the following steps: (1) Preparation of activated graphene powder: Graphene was placed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:0.5, with a solid-liquid ratio of 1:30 g / mL, and stirred at a constant temperature of 65℃ for 4h. After the reaction was completed, the graphene was washed with deionized water by centrifugation until the filtrate was neutral, dried under vacuum at 70℃ for 6h, and then ground to obtain activated graphene powder. (2) Preparation of graphene-based ternary composite powder: Activated graphene powder was dispersed in deionized water at a mass-volume ratio of 1g:50mL and ultrasonically dispersed for 45min; the pH of the system was adjusted to 9.0 with ammonia water and kept in a constant temperature water bath at 75℃; ZrOCl2·8H2O was added first and stirred at a constant temperature for 3h, then Ce(NO3)3·6H2O was added and stirred at a constant temperature for another 3h, and then allowed to stand for aging for 1.5h; after centrifugation, the powder was washed 4 times with deionized water, dried at 70℃ for 8h, and then calcined at 500℃ for 3h, ground and sieved to obtain graphene-based ternary composite powder; the mass ratio of activated graphene, ZrOCl2·8H2O and Ce(NO3)3·6H2O was 1:0.5:0.3; (3) Preparation of high-load deodorization masterbatch: Graphene-based ternary composite powder, polypropylene (PP) matrix resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S), and maleic anhydride-grafted PP interface compatibilizer were mixed at a mass ratio of 5:94:1 and added to a high-speed mixer and mixed at 90°C for 15 min; then fed into a twin-screw extruder for melt blending, with an extrusion temperature of 185°C and a screw speed of 150 r / min; after water cooling, pelletizing, and drying, high-load deodorization masterbatch was obtained. (4) Preparation of graphene deodorized monofilament: The deodorization masterbatch and pure PP resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S) were mixed uniformly at a mass ratio of 10:90 and fed into a melt spinning equipment; the spinning temperature was 195℃, the single hole diameter of the spinneret was 0.2mm, and after spinning, the spinneret was stretched with a stretch ratio of 5 times and a winding speed of 110m / min to obtain graphene deodorized monofilament; (5) Warp drawing treatment: The graphene deodorized monofilaments are drawn and treated at a speed of 800 m / min and the monofilament tension is controlled at 0.10~0.30 cN / dtex to obtain uniform and stable warp and weft yarns; (6) Warp and weft interlacing to form a net: the warp and weft yarns after being drawn are introduced into a high-speed rapier loom, and the loom speed is controlled at 10-20m / min. The warp and weft yarns are interlaced to form a filter net fabric; the warp and weft density of the finished filter net is 33±2×0±2 threads / inch; (7) Heat setting treatment: The filter fabric is sent into the heat setting equipment, the setting temperature is 135℃, and the heat setting is maintained for 20s to improve the dimensional stability of the fabric and the cross-bonding strength of the filaments, so as to obtain the graphene-based deodorizing filter.

[0038] Comparative Example 1 (no rare earth elements, only graphene + zirconium): A method for preparing a graphene-based deodorizing filter, comprising the following steps: (1) Preparation of activated graphene powder: Graphene was placed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:0.5, with a solid-liquid ratio of 1:30 g / mL, and stirred at a constant temperature of 65℃ for 4h. After the reaction was completed, the graphene was washed with deionized water by centrifugation until the filtrate was neutral, dried under vacuum at 70℃ for 6h, and then ground to obtain activated graphene powder. (2) Preparation of graphene-based composite powder: Activated graphene powder was dispersed in deionized water at a mass-volume ratio of 1g:50mL and ultrasonically dispersed for 45min; the pH of the system was adjusted to 9.0 with ammonia water and kept at a constant temperature of 75℃ in a water bath; ZrOCl2·8H2O was added and stirred at a constant temperature for 3h, and then allowed to stand for aging for 1.5h; after centrifugation, the powder was washed 4 times with deionized water, dried at 70℃ for 8h, and then calcined at 500℃ for 3h. The powder was then ground and sieved to obtain graphene-based composite powder; the mass ratio of activated graphene to ZrOCl2·8H2O was 1:1.5. (3) Preparation of high-load deodorization masterbatch: Graphene-based composite powder, polypropylene (PP) matrix resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S), and maleic anhydride-grafted PP interface compatibilizer were mixed at a mass ratio of 7:91.5:1.5 and added to a high-speed mixer and mixed at 90°C for 15 min; then fed into a twin-screw extruder for melt blending, with an extrusion temperature of 185°C and a screw speed of 150 r / min; after water cooling, pelletizing, and drying, high-load deodorization masterbatch was obtained. (4) Preparation of graphene deodorized monofilament: The deodorization masterbatch and pure PP resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S) were mixed uniformly at a mass ratio of 12:88 and fed into a melt spinning equipment; the spinning temperature was 195℃, and after spinning, the fibers were stretched with a stretch ratio of 5 times and a winding speed of 110m / min to obtain graphene deodorized monofilament; (5) Warp drawing treatment: The graphene deodorized monofilaments are drawn and treated at a speed of 800 m / min and the monofilament tension is controlled at 0.10~0.30 cN / dtex to obtain uniform and stable warp and weft yarns; (6) Warp and weft interlacing to form a net: the warp and weft yarns after being drawn are introduced into a high-speed rapier loom, the loom speed is controlled at 15m / min, and the warp and weft interlacing is used to form a filter net fabric; the warp and weft density of the finished filter net is 33±×30±2 threads / inch; (7) Heat setting treatment: The filter fabric is sent into the heat setting equipment, the setting temperature is 135℃, and the heat setting is maintained for 20s to improve the dimensional stability of the fabric and the cross-bonding strength of the filaments, so as to obtain the graphene-based deodorizing filter.

[0039] Comparative Example 2 (no zirconium-based, only graphene + rare earth elements): A method for preparing a graphene-based deodorizing filter, comprising the following steps: (1) Preparation of activated graphene powder: Graphene was placed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:0.5, with a solid-liquid ratio of 1:30 g / mL, and stirred at a constant temperature of 65℃ for 4h. After the reaction was completed, the graphene was washed with deionized water by centrifugation until the filtrate was neutral, dried under vacuum at 70℃ for 6h, and then ground to obtain activated graphene powder. (2) Preparation of graphene-based composite powder: Activated graphene powder was dispersed in deionized water at a mass-volume ratio of 1g:50mL and ultrasonically dispersed for 45min; the pH of the system was adjusted to 9.0 with ammonia water and kept at a constant temperature of 75℃ in a water bath; Ce(NO3)3·6H2O was added and stirred at a constant temperature for 3h, and then allowed to stand for aging for 1.5h; after centrifugation, the powder was washed 4 times with deionized water, dried at 70℃ for 8h, and then calcined at 500℃ for 3h. The powder was then ground and sieved to obtain graphene-based composite powder; the mass ratio of activated graphene to Ce(NO3)3·6H2O was 1:0.8. (3) Preparation of high-load deodorization masterbatch: Graphene-based composite powder, polypropylene (PP) matrix resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S), and maleic anhydride-grafted PP interface compatibilizer were mixed at a mass ratio of 7:91.5:1.5 and added to a high-speed mixer and mixed at 90°C for 15 min; then fed into a twin-screw extruder for melt blending, with an extrusion temperature of 185°C and a screw speed of 150 r / min; after water cooling, pelletizing, and drying, high-load deodorization masterbatch was obtained. (4) Preparation of graphene deodorized monofilament: The deodorization masterbatch and pure PP resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S) were mixed uniformly at a mass ratio of 12:88 and fed into a melt spinning equipment; the spinning temperature was 195℃, and after spinning, the fibers were stretched with a stretch ratio of 5 times and a winding speed of 110m / min to obtain graphene deodorized monofilament; (5) Warp drawing treatment: The graphene deodorized monofilaments are drawn and treated at a speed of 800 m / min and the monofilament tension is controlled at 0.10~0.30 cN / dtex to obtain uniform and stable warp and weft yarns; (6) Warp and weft interlacing to form a net: the warp and weft yarns after being drawn are introduced into a high-speed rapier loom, the loom speed is controlled at 15m / min, and the warp and weft interlacing is used to form a filter net fabric; the warp and weft density of the finished filter net is 33±×30±2 threads / inch; (7) Heat setting treatment: The filter fabric is sent into the heat setting equipment, the setting temperature is 135℃, and the heat setting is maintained for 20s to improve the dimensional stability of the fabric and the cross-bonding strength of the filaments, so as to obtain the graphene-based deodorizing filter.

[0040] Comparative Example 3 (graphene only): A method for preparing a graphene-based deodorizing filter, comprising the following steps: (1) Preparation of activated graphene powder: Graphene was placed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:0.5, with a solid-liquid ratio of 1:30 g / mL, and stirred at a constant temperature of 65℃ for 4h. After the reaction was completed, the graphene was washed with deionized water by centrifugation until the filtrate was neutral, dried under vacuum at 70℃ for 6h, and then ground to obtain activated graphene powder. (2) Preparation of high-load deodorization masterbatch: Activated graphene powder, polypropylene (PP) matrix resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S), and maleic anhydride grafted PP interface compatibilizer were mixed at a mass ratio of 7:91.5:1.5 and added to a high-speed mixer and mixed at 90°C for 15 min; then fed into a twin-screw extruder for melt blending, with an extrusion temperature of 185°C and a screw speed of 150 r / min; after water cooling, pelletizing, and drying, high-load deodorization masterbatch was obtained. (3) Preparation of graphene deodorized monofilament: The deodorization masterbatch and pure PP resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S) were mixed uniformly at a mass ratio of 12:88 and fed into a melt spinning equipment; the spinning temperature was 195℃, and after spinning, the fibers were stretched with a stretch ratio of 5 times and a winding speed of 110m / min to obtain graphene deodorized monofilament; (4) Warp drawing treatment: The graphene deodorized monofilaments are drawn and treated at a speed of 800 m / min and the monofilament tension is controlled at 0.10~0.30 cN / dtex to obtain uniform and stable warp and weft yarns; (5) Warp and weft interlacing to form a net: the warp and weft yarns after being drawn are introduced into a high-speed rapier loom, the loom speed is controlled at 15m / min, and the warp and weft interlacing is used to form a filter net fabric; the warp and weft density of the finished filter net is 33±×30±2 threads / inch; (6) Heat setting treatment: The filter fabric is sent into the heat setting equipment, the setting temperature is 135℃, and the heat setting is maintained for 20s to improve the dimensional stability of the fabric and the cross-bonding strength of the filaments, so as to obtain the graphene-based deodorizing filter.

[0041] Comparative Example 4 (graphene directly mixed with adsorbent and catalyst): A method for preparing a graphene-based deodorizing filter, comprising the following steps: (1) Preparation of activated graphene powder: Graphene was placed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:0.5, with a solid-liquid ratio of 1:30 g / mL, and stirred at a constant temperature of 65℃ for 4h. After the reaction was completed, the graphene was washed with deionized water by centrifugation until the filtrate was neutral, dried under vacuum at 70℃ for 6h, and then ground to obtain activated graphene powder. (2) Preparation of graphene-based ternary mixed powder: Activated graphene, zirconium hydroxide and cerium oxide are mixed evenly at a mass ratio of 1:1.5:0.8 to obtain graphene-based ternary mixed powder; (3) Preparation of high-load deodorization masterbatch: Graphene-based ternary mixed powder, polypropylene (PP) matrix resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S), and maleic anhydride-grafted PP interface compatibilizer were mixed at a mass ratio of 7:91.5:1.5 and added to a high-speed mixer and mixed at 90°C for 15 min; then fed into a twin-screw extruder for melt blending, with an extrusion temperature of 185°C and a screw speed of 150 r / min; after water cooling, pelletizing, and drying, high-load deodorization masterbatch was obtained. (4) Preparation of graphene deodorized monofilament: The deodorization masterbatch and pure PP resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S) were mixed uniformly at a mass ratio of 12:88 and fed into a melt spinning equipment; the spinning temperature was 195℃, and after spinning, the fibers were stretched with a stretch ratio of 5 times and a winding speed of 110m / min to obtain graphene deodorized monofilament; (5) Warp drawing treatment: The graphene deodorized monofilaments are drawn and treated at a speed of 800 m / min and the monofilament tension is controlled at 0.10~0.30 cN / dtex to obtain uniform and stable warp and weft yarns; (6) Warp and weft interlacing to form a net: the warp and weft yarns after being drawn are introduced into a high-speed rapier loom, the loom speed is controlled at 15m / min, and the warp and weft interlacing is used to form a filter net fabric; the warp and weft density of the finished filter net is 33±×30±2 threads / inch; (7) Heat setting treatment: The filter fabric is sent into the heat setting equipment, the setting temperature is 135℃, and the heat setting is maintained for 20s to improve the dimensional stability of the fabric and the cross-bonding strength of the filaments, so as to obtain the graphene-based deodorizing filter.

[0042] Comparative Example 5 (changing the depositional order of zirconium series and rare earth elements): A method for preparing a graphene-based deodorizing filter, comprising the following steps: (1) Preparation of activated graphene powder: Graphene was placed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid at a volume ratio of 1:0.5, with a solid-liquid ratio of 1:30 g / mL, and stirred at a constant temperature of 65℃ for 4h. After the reaction was completed, the graphene was washed with deionized water by centrifugation until the filtrate was neutral, dried under vacuum at 70℃ for 6h, and then ground to obtain activated graphene powder. (2) Preparation of graphene-based ternary composite powder: Activated graphene powder was dispersed in deionized water at a mass-volume ratio of 1g:50mL and ultrasonically dispersed for 45min; the pH of the system was adjusted to 9.0 with ammonia water and kept at a constant temperature of 75℃ in a water bath; Ce(NO3)3·6H2O was added first and stirred at a constant temperature for 3h, then ZrOCl2·8H2O was added and stirred at a constant temperature for another 3h, and then allowed to stand for aging for 1.5h; after centrifugation, the powder was washed 4 times with deionized water, dried at 70℃ for 8h, and then calcined at 500℃ for 3h, ground and sieved to obtain graphene-based ternary composite powder; the mass ratio of activated graphene, ZrOCl2·8H2O and Ce(NO3)3·6H2O was 1:1.5:0.8; (3) Preparation of high-load deodorization masterbatch: Graphene-based ternary composite powder, polypropylene (PP) matrix resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S), and maleic anhydride-grafted PP interface compatibilizer were mixed at a mass ratio of 7:91.5:1.5 and added to a high-speed mixer and mixed at 90°C for 15 min; then fed into a twin-screw extruder for melt blending, with an extrusion temperature of 185°C and a screw speed of 150 r / min; after water cooling, pelletizing, and drying, high-load deodorization masterbatch was obtained. (4) Preparation of graphene deodorized monofilament: The deodorization masterbatch and pure PP resin (Sinopec Zhenhai Refining & Chemical, PPH-T30S) were mixed uniformly at a mass ratio of 12:88 and fed into a melt spinning equipment; the spinning temperature was 195℃, and after spinning, the fibers were stretched with a stretch ratio of 5 times and a winding speed of 110m / min to obtain graphene deodorized monofilament; (5) Warp drawing treatment: The graphene deodorized monofilaments are drawn and treated at a speed of 800 m / min and the monofilament tension is controlled at 0.10~0.30 cN / dtex to obtain uniform and stable warp and weft yarns; (6) Warp and weft interlacing to form a net: the warp and weft yarns after being drawn are introduced into a high-speed rapier loom, the loom speed is controlled at 15m / min, and the warp and weft interlacing is used to form a filter net fabric; the warp and weft density of the finished filter net is 33±×30±2 threads / inch; (7) Heat setting treatment: The filter fabric is sent into the heat setting equipment, the setting temperature is 135℃, and the heat setting is maintained for 20s to improve the dimensional stability of the fabric and the cross-bonding strength of the filaments, so as to obtain the graphene-based deodorizing filter.

[0043] The removal efficiency of the graphene-based deodorizing filters prepared in the above embodiments and comparative examples for ammonia, acetic acid, and acetaldehyde was tested. The method was as follows: based on the JEM1467 standard, the graphene deodorizing filter was installed in an air conditioner and then placed at a depth of 1m. 3In an environmental test chamber, five cigarettes were lit, producing ammonia, acetic acid, and acetaldehyde. The chamber door was then closed, and after the cigarettes had completely burned, the initial gas concentrations were measured. The air conditioning was then turned on, and the remaining concentrations of ammonia, acetic acid, and acetaldehyde were measured after one hour. The removal rates of ammonia, acetic acid, and acetaldehyde by the graphene deodorization network were calculated, and the results are shown in Table 1.

[0044] Table 1: Deodorization performance test results of graphene deodorizing filter

[0045] As shown in Table 1, the filters obtained using the graphene-based ternary composite powder of this invention in Examples 1-3 exhibit high removal rates for ammonia, acetic acid, and acetaldehyde. The overall scheme of this invention—combining the three components, two-step in-situ layered loading, a masterbatch loading of 5-10%, and a spinning-limited addition range of 10-15%—achieves simultaneous and efficient removal of all three gases. In Comparative Example 1, without rare earth catalysts, the composite powder showed excellent adsorption performance for ammonia and acetic acid, but its catalytic decomposition ability for acetaldehyde decreased significantly, making it unable to treat organic odors. In Comparative Example 2, without zirconium-based adsorbents, the composite powder showed good catalytic effect on acetaldehyde, but its selective adsorption capacity for ammonia and acetic acid was significantly insufficient. In Comparative Example 3, with only graphene added, the removal rates for all three gases were low, indicating that efficient simultaneous deodorization could not be achieved solely through physical adsorption. In Comparative Example 4, graphene, zirconium-based adsorbent, and rare earth catalyst were physically mixed without loading. Due to the weak physical contact between the three components, no chemical bonds were formed. This resulted in severe agglomeration of the zirconium and rare earth particles during the high-temperature, high-shear melt spinning process. A large number of active sites were encapsulated inside the particles and could not be exposed to the gas, leading to low utilization and a simultaneous decrease in the removal rates of ammonia, acetic acid, and acetaldehyde. In Comparative Example 5, the loading order of the zirconium-based adsorbent and rare earth catalyst was changed. Because Zr... 4+ The binding energy of functional groups on the graphene surface is significantly higher than that of rare earth ions. Although the rare earth ions added first occupy some sites, the binding is weak. The large amount of zirconium added later cannot be effectively chemically anchored because the strongest anchoring sites have been occupied. It can only be non-selectively deposited on the rare earth surface or self-nucleated and aggregated in the solution. This leads to a decrease in the ability of zirconium to adsorb ammonia and acetic acid. At the same time, the rare earth catalytic sites are covered and electron transport is blocked, resulting in a decrease in the acetaldehyde removal rate.

[0046] Using Example 2 as the test sample, the durability of the deodorizing filter was tested. The method was as follows: Following the water washing standard GB / T 46496-2025 Kitchen Air Conditioners, two consecutive deodorization tests were conducted, followed by water washing, and this process was repeated twice more to simulate the recovery of the deodorizing effect after use and subsequent water washing. Figure 3 As shown in Table 2.

[0047] Table 2: Changes in deodorization performance after multiple tests and washing with water

[0048] from Figure 3 As can be seen, the deodorization performance of the same mesh decreased after multiple deodorization tests, but it could be partially restored after washing with water. This indicates that the graphene deodorization mesh has a certain degree of durability; its deodorization performance decreases during long-term use, but the effect will be significantly restored after thorough washing with water.

[0049] It should be noted that the specific implementation methods described above provide a detailed explanation of the technical solution and application results of the present invention. The above embodiments are only the most preferred embodiments and are not intended to limit the present invention. Modifications or equivalent substitutions made by those skilled in the art within the core theoretical scope of the present invention should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a graphene-based composite masterbatch, characterized by comprising: The following steps are required: (1) Activated graphene is obtained by activating graphene with an acid solution; (2) Activated graphene is dispersed in a solvent, zirconium-based precursor raw material is added for in-situ precipitation, and then rare earth precursor raw material is added for further in-situ precipitation. The resulting product is separated, washed, dried and calcined to obtain graphene-based ternary composite powder. (3) The graphene-based ternary composite powder is mixed with the matrix resin and compatibilizer, and then melt-blended, extruded and pelletized to obtain the graphene-based composite masterbatch.

2. The method for preparing graphene-based composite masterbatch according to claim 1, characterized in that, The acid solution mentioned in step (1) is a mixture of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:0.3-0.

8. The solid-liquid ratio of the activation treatment is 1g:20-50mL, the activation temperature is 50-80℃, and the activation time is 2-6h.

3. The method for preparing graphene-based composite masterbatch according to claim 1, characterized in that, The zirconium-based precursor raw material mentioned in step (2) is a soluble zirconium salt; the rare earth precursor raw material is a soluble salt of cerium and / or lanthanum; the mass ratio of activated graphene, zirconium-based precursor raw material and rare earth precursor raw material is 1:0.5-3:0.3-2.

4. The method for preparing graphene-based composite masterbatch according to claim 1 or 3, characterized in that, The solvent mentioned in step (2) is deionized water. After adding zirconium-based precursor raw materials and rare earth precursor raw materials, the mixture is first ultrasonically dispersed for 30-60 minutes, and then the pH value is adjusted to 8.0-10.

0. The mixture is then precipitated in situ at 60-90℃ for 2-h. After the second in-situ precipitation reaction, the mixture is aged for 1-2 hours. The calcination temperature is 400-600℃ and the calcination time is 2-4 hours.

5. The method for preparing graphene-based composite masterbatch according to claim 1, characterized in that, In step (3), by mass percentage, 5-10% graphene-based ternary composite powder, 88-94% matrix resin, and 1-2% compatibilizer are added.

6. A graphene-based composite masterbatch, characterized in that, It is prepared by any one of the preparation methods described in claims 1 to 5.

7. The application of the graphene-based composite masterbatch as described in claim 6 in a deodorizing filter, characterized in that, The deodorizing filter is prepared by: S1: The graphene-based composite masterbatch is used for melt spinning to obtain deodorized monofilament; S2: The obtained deodorized monofilaments are subjected to warp drawing treatment to form weavable warp and weft yarns; S3: The warp and weft yarns are interwoven into a mesh, and the deodorizing filter mesh is obtained after heat setting.

8. The application of the graphene-based composite masterbatch according to claim 7 in a deodorizing filter, characterized in that, In S1, graphene composite masterbatch is mixed with resin matrix and melt-spun to produce deodorizing monofilament; or graphene composite masterbatch is used as the skin layer and resin matrix is ​​used as the core layer, and melt-spun to produce skin-core type deodorizing monofilament.

9. The application of the graphene-based composite masterbatch according to claim 7 in a deodorizing filter, characterized in that, The traction speed in S2 is 500-1500 m / min.

10. The application of the graphene-based composite masterbatch according to claim 7 in a deodorizing filter, characterized in that, The warp and weft density of the S3 mesh is 33±2*30±2Pcs / inch; the heat setting temperature is 120-150℃, and the setting time is 10-30s.

Citation Information

Patent Citations

  • Photocatalytic material for air filtering screens, preparation method and applications thereof

    CN110433870A